2007
DOI: 10.1108/10444060710759309
|View full text |Cite
|
Sign up to set email alerts
|

Conflict management styles: the differences among the Chinese, Japanese, and Koreans

Abstract: PurposeThe purpose of this paper is to examine how the Chinese, Japanese, and Koreans resolve an interpersonal conflict with their supervisors and how cultural factors explain the differences in conflict management styles.Design/methodology/approachA survey was conducted involving 275 employees from China, Japan and South Korea. A hierarchical regression analysis and A‐matrix hypothesis test were used to analyze the data.FindingsKoreans, compared with the Chinese and Japanese, were more likely to use a comprom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(83 citation statements)
references
References 34 publications
3
78
1
1
Order By: Relevance
“…One potential explanation for the mixed findings might be that previous studies have often failed to consider the culture-specific pattern of emotional intelligence (Gunkel, Schlä gel, & Engle, 2014;Miller, 1997;Shao, Doucet, & Caruso, 2014). While previous studies have shown that preferences for conflict handling styles vary substantially across countries (e.g., Doucet, Jehn, Weldon, Chen, & Wang, 2009;Gabrielidis, Stephan, Ybarra, Pearson, & Villareal, 1997;Kim, Wang, Kondo, & Kim, 2007;Posthuma, White, Dworkin, Yá nez, & Swift, 2006;Ting-Toomey et al, 1991), only a small number of studies (e.g., Kaushal & Kwantes, 2006;Komarraju, Dollinger, & Lovell, 2008;Morris et al, 1998) has analyzed the underlying reasons for these differences. Prior research suggests that differences in individuals' orientation toward different cultural value dimensions (i.e., the set of aspects that characterize a society according to its apparent place within the continuum of patterns described by the respective aspect) may be one promising explanation for cross-country differences in individual preferences for conflict handling styles (e.g., Holt & DeVore, 2005;Komarraju et al, 2008).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One potential explanation for the mixed findings might be that previous studies have often failed to consider the culture-specific pattern of emotional intelligence (Gunkel, Schlä gel, & Engle, 2014;Miller, 1997;Shao, Doucet, & Caruso, 2014). While previous studies have shown that preferences for conflict handling styles vary substantially across countries (e.g., Doucet, Jehn, Weldon, Chen, & Wang, 2009;Gabrielidis, Stephan, Ybarra, Pearson, & Villareal, 1997;Kim, Wang, Kondo, & Kim, 2007;Posthuma, White, Dworkin, Yá nez, & Swift, 2006;Ting-Toomey et al, 1991), only a small number of studies (e.g., Kaushal & Kwantes, 2006;Komarraju, Dollinger, & Lovell, 2008;Morris et al, 1998) has analyzed the underlying reasons for these differences. Prior research suggests that differences in individuals' orientation toward different cultural value dimensions (i.e., the set of aspects that characterize a society according to its apparent place within the continuum of patterns described by the respective aspect) may be one promising explanation for cross-country differences in individual preferences for conflict handling styles (e.g., Holt & DeVore, 2005;Komarraju et al, 2008).…”
mentioning
confidence: 99%
“…By directly measuring the full set of cultural value dimensions across a large number of countries and cultural regions the present study overcomes these limitations. Kim et al (2007) Power distance Integrating, obliging, avoiding, compromising, dominanting Cultural dimension is directly measured; respondents from three countries (China, Japan, and Korea) Kim & Meyers (2012) Holism Accommodating, avoidance, competing, collaborating, compromising…”
Section: Appendix Amentioning
confidence: 99%
“…Ting-Toomey et al (1991) conducted a questionnaire survey comparing American, Chinese, Japanese, Korean, and Taiwanese students, noting that (a) Chinese prefer obliging, dominating, and avoiding more than Japanese and Koreans; (b) Chinese and Koreans prefer integrating and compromising more than Japanese; and (c) Japanese prefer obliging more than Koreans. Kim, Wang, Kondo, and Kim (2007) looked at conflict management styles of corporate subordinates and supervisors and found that Japanese use obliging styles more than Chinese and Koreans, whereas Koreans use compromising styles more than Chinese and Japanese. Yi and Park (2003) observed decision-making styles within interpersonal conflict among Americans, Canadians, Chinese, Japanese, and Koreans in their questionnaire survey and discovered that Koreans preferred dominating and obliging styles, whereas Japanese scored low on all styles relative to the other cultures.…”
Section: Cultural Difference In Conflict Management Strategies In Chimentioning
confidence: 98%
“…Lee, 2003;Trubisky et al, 1991). Kim et al (2007) compared three different groups in terms of conflict management strategies at the workplace and found that the compromising strategy was used often when conflicts existed between employees and supervisors. The compromising strategy may produce beneficial results due to the fact that this strategy helps conflicting people quickly find solutions and provide benefits to both sides through concessions (Hocker and Wilmot, 1998;Gross and Guerrero, 2000;Rahim, 2002).…”
Section: Conflict Management Grid (Cmg)mentioning
confidence: 99%